Association Between Sleeping Quality and Risk of Breast Cancer Among Women: A Case-Control Study From Pakistan - Huma Naqeeb; Zia-Ud-Din; Imran Khan; Ijaz-ul Haq; Falak Zeb; Bibi Hajira; Iftikhar Alam; Zafar Iqbal; Rehana Masood; Muhammad Aftab (Cancer Control)
Background This case-control study investigated the relationship between sleep duration and quality with the occurrence of breast cancer among women, both pre- and post-menopausal, in the northwest Khyber Pakhtunkhwa (KP) region of Pakistan. Method This case-control research was carried in multiple tertiary care facilities. Newly diagnosed primary breast cancer patients were recruited as cases (n = 408), and 5+ years age-matched controls (n = 408) were randomly selected from the general population. Participants completed a Pittsburg sleeping quality index (PSQI) questionnaire that included questions on sleep characteristics. Statistical analysis included independent t-tests to compare mean sleep durations and quality scores between groups, and logistic regression to adjust for potential confounders. Results Sleep onset latency between cases and controls was not significantly associated with health outcomes, with a P -value of .142. However, sleep duration showed a significant association ( P = .049). For sleep duration, the adjusted odds ratio for ≤6 h was 1.02 (95% CI: .5-2.1), while for 7-8 h the adjusted odds ratio was 1.0 (95% CI: .6-1.6). Self-reported sleep quality did not demonstrate significant associations, with the P -value for “very good” sleep quality being .561. Sleep duration of less than 6 h among women with triple-negative breast cancer (TNBC) was found to be strongly associated with a more aggressive type of breast cancer, with an adjusted odds ratio of 1.5 (95% CI: 1.02-2.3, P < .05). Conclusion This study does not provide evidence to support an association between sleep duration or quality and the risk of breast cancer. However, it reports a significant association, with shorter sleep durations linked to an increased risk particularly in the context of aggressive breast cancer types such as TNBC.